An Automated Feeding System Model to Improve Production Efficiency in Laying Hens - Jumadil Hadi; Yunxiao Jiang (Journal of Animal Husbandry, 2026)
The poultry industry continues to seek technological innovations to improve production efficiency and reduce operational costs. One critical aspect in poultry farming is feed management, which significantly influences productivity and farm sustainability. Manual feeding systems often lead to feed waste, labor inefficiency, and inconsistent feeding schedules. This study aims to develop an automated feeding system model to improve production efficiency in laying hens through the integration of Internet of Things (IoT) technology and real-time monitoring systems. The research employed a system development approach combining microcontroller-based automation, sensor monitoring, and scheduling mechanisms using real-time clock modules. Data were analyzed by comparing feeding accuracy, labor efficiency, and feed utilization before and after system implementation. The results demonstrate that the proposed automated feeding model improves feeding accuracy and reduces feed waste while maintaining optimal feeding intervals. The integration of sensors and IoT monitoring also enables real-time control and improved farm management. The findings indicate that automated feeding technology contributes significantly to enhancing production efficiency and sustainability in poultry farming. This study provides a practical model that can be implemented in small- and medium-scale poultry farms to support modern poultry management systems.